Act of March 23, 1935, ch. 172, § 8, Wash. Sess. Laws 599, 601. - (:unkn) unknown (My University, 1935)
No person shall deliver a pistol to any person under the age of twenty-one or to one who he has reasonable cause to believe has been convicted of a crime of violence, or is a drug addict, an habitual drunkard, or of unsound mind."
Keywords: TRANSFER - MINORS